Salt sensor device and manufacturing method thereof
By covering the inorganic organic composite film with multi-layer metal nanoparticle layer and multi-layer multivalent ion layer outside the heteronuclear part of the optical fiber sensor, the problem of difficulty in monitoring the adhesion amount of salt substances in the prior art is solved, and high sensitivity to detection of salt substance concentration is achieved.
Patent Information
- Application Number
- JP2021009149
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-22
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-01-22
AI Technical Summary
It is difficult for the existing technology to monitor the adhesion of salt substances (such as sodium chloride) in existing infrastructure in real time for a long time, and it cannot effectively solve the corrosion problem caused by infrastructure due to salt substances.
A salt sensor device is used, which includes an optical fiber sensor. The heteronuclear part of the optical fiber sensor is covered with an inorganic organic composite film with a multi-layer metal nanoparticle layer and a multi-layer multivalent ion layer. This design detects the concentration of salt substances by changing the refractive index of the multivalent ion layer.
This design significantly improves the sensitivity of salt substance concentration detection, can monitor the adhesion amount of salt substances in a long time, effectively solving the monitoring problem of infrastructure corrosion problems.
Smart Images

Figure 0007650456000002 
Figure 0007650456000003 
Figure 0007650456000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a salt sensor device and a manufacturing method thereof. [Background technology]
[0002] 2. Description of the Related Art Conventionally, as a sensor device using an optical fiber, for example, an optical fiber device in which gold nanoparticles are fixed to the outer peripheral surface of the cladding of a heterocore portion of an optical fiber is known (see, for example, Patent Document 1).
[0003] The optical fiber device described in Patent Document 1 is configured such that, when light is transmitted from a light transmission section through the heterocore section to the optical fiber, the degree of absorption of light of a predetermined wavelength in the near-infrared region in the heterocore section changes depending on the refractive index of the material surrounding the heterocore section. As a result, the optical fiber device makes it possible to measure characteristics such as the refractive index and concentration of the material surrounding the heterocore section with high sensitivity by measuring the degree of attenuation of the propagation intensity of light of a wavelength in the near-infrared region in the optical fiber. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 6391305 Summary of the Invention [Problem to be solved by the invention]
[0005] Incidentally, it is known that sodium chloride contained in seawater and antifreeze agents can cause deterioration of concrete and steel frames in public infrastructure such as bridges and tunnels, and in architectural facilities such as buildings. For this reason, it is necessary to capture changes in the amount of sodium chloride attached over time in order to manage these deterioration.
[0006] Conventionally, known methods for detecting sodium chloride include a method for measuring the electrical conductivity of a sodium chloride solution, optical spectroscopy, a flame color reaction method, and atomic absorption spectrometry.
[0007] However, all of the above detection methods require sampling of a sample containing sodium chloride from the target object, and have the problem that it is not possible to observe in situ over a long period of time the change in the amount of sodium chloride attached to existing infrastructure, buildings, etc.
[0008] In order to solve the above problems, the present inventors have proposed a salt sensor device that can observe the amount of salt such as sodium chloride in situ over a long period of time (see Patent Application No. 2019-149024).
[0009] The salt sensor device includes a light transmission section having a core and a clad, a heterocore section having a core and a clad respectively connected to the core and clad of the light transmission section, an optical fiber having a core of the heterocore section having a smaller diameter than the core of the light transmission section, a metal nanoparticle layer dispersed and fixed to the outer peripheral surface of the clad of the heterocore section, and an alternating laminated film layer covering the metal nanoparticle layer. In the salt sensor device, the metal nanoparticle layer is only one layer, and the alternating laminated film layer is formed by alternately laminating at least one layer each of a polycation film and a polyanion film.
[0010] In the salt sensor device, when light is transmitted through the core of the optical transmission section, the light leaking into the clad in the heterocore section is totally reflected at the interface between the clad and the outside world, and evanescent light seeps out to the outside world. When the evanescent light resonates with the collective oscillation of electrons in the metal nanoparticles of the metal nanoparticle layer, the evanescent light is absorbed, and the reflected light totally reflected at the interface is reduced, but the degree of reduction depends on the refractive index of the polyion layer.
[0011] Therefore, according to the salt sensor device, the concentration of salt present in the outside world of the heterocore part can be known by detecting the degree of reduction in light totally reflected at the interface between the cladding of the heterocore part and the outside world.
[0012] However, it is desirable to develop a salt sensor device that can further increase its sensitivity to salt concentration.
[0013] In view of the above circumstances, the present invention aims to provide a salt sensor device that can monitor the amount of salt such as sodium chloride in situ over a long period of time and further increase the sensitivity to salt concentration, and a manufacturing method thereof. [Means for solving the problem]
[0014] In order to achieve this object, the salt sensor device of the present invention is a salt sensor device comprising an optical fiber having a light transmission section having a core and a clad, and a heterocore section having a core and a clad respectively connected to the core and the clad of the light transmission section, the core of the heterocore section having a smaller diameter than the core of the light transmission section, and the salt sensor device comprises an inorganic-organic composite laminated film formed by alternately laminating a plurality of metal nanoparticle layers and a plurality of polyion layers covering the metal nanoparticle layers on the outer peripheral surface of the clad of the heterocore section. The polyion layer is made of a polycation selected from the group consisting of vinylpyrrolidone-N,N-dimethylaminoethyl methacrylic acid copolymer diethyl sulfate, chitosan, diethylaminoethyl dextran, diallylamine hydrochloride polymer, methyl diallylamine hydrochloride polymer, diethylaminoethyl cellulose, and dextran chloride hydroxypropyltrimethylammonium ether, or a polyanion selected from the group consisting of polyglutamic acid and its salts, carboxymethyl dextran, carboxymethyl cellulose, hyaluronic acid and its salts, and alginic acid and its salts. It is characterized by:
[0015] The "salt" to be detected by the salt sensor of the present invention means a compound formed by ionic bonding between a cation and an anion. Examples of the cation include hydrogen ions, sodium ions, potassium ions, calcium ions, etc., and examples of the anion include fluoride ions, chloride ions, bromide ions, iodide ions, sulfate ions, nitrate ions, etc. Examples of the "salt" as a compound formed by ionic bonding between the cation and the anion include sodium chloride and calcium chloride.
[0016] In the salt sensor device of the present invention, similarly to the salt sensor device described in Japanese Patent Application No. 2019-149024, when light is transmitted through the core of the light transmission unit, when the light leaking into the clad in the heterocore portion is totally reflected at the interface between the clad and the outside world, the evanescent light leaking out to the outside world resonates with the collective vibration of the electrons in the metal nanoparticles of the metal nanoparticle layer, and the evanescent light is absorbed, and the reflected light totally reflected at the interface is reduced. Here, the degree of reduction in the reflected light depends on the refractive index of the polyion layer, and the refractive index of the polyion layer changes depending on the concentration of salt present in the outside world of the heterocore portion. Therefore, both the salt sensor device of the present invention and the salt sensor device described in Japanese Patent Application No. 2019-149024 can detect the degree of reduction in the light totally reflected at the interface between the clad of the heterocore portion and the outside world, thereby knowing the concentration of salt present in the outside world of the heterocore portion.
[0017] In this case, the salt sensor device described in Japanese Patent Application No. 2019-149024 has only one metal nanoparticle layer on the outer peripheral surface of the clad of the heterocore portion, whereas the salt sensor device of the present invention has a plurality of metal nanoparticle layers stacked vertically as the inorganic-organic composite laminated film, and the amount of the metal nanoparticles is significantly increased compared to the salt sensor device described in Japanese Patent Application No. 2019-149024. Therefore, according to the salt sensor device of the present invention, it is possible to further increase the sensitivity to salt concentration compared to the salt sensor device described in Japanese Patent Application No. 2019-149024.
[0018] In the salt sensor device of the present invention, the inorganic-organic composite laminated film is preferably formed by alternating 2 to 2,000 layers of the metal nanoparticle layers and the polyion layers in order to further increase the sensitivity to salt concentration compared to the salt sensor device described in Japanese Patent Application No. 2019-149024.
[0019] In the salt sensor device of the present invention, the metal nanoparticles constituting the metal nanoparticle layer preferably have a particle diameter in the range of, for example, 5 to 100 nm, and the metal nanoparticles are preferably gold nanoparticles.
[0021] In the salt sensor device of the present invention, when the polyion layer is a polycation layer, the polycation layer is positively charged and has anions as counterions. When salt is present in the outside of the heterocore portion, the anions constituting the salt exchange with the anions contained in the polycation layer, and depending on the concentration of the salt, the anions constituting the salt penetrate into the polycation layer. As a result, the polycation layer swells or shrinks, changing the refractive index.
[0022] On the other hand, in the salt sensor device of the present invention, when the polyion layer is a polyanion layer, the polyanion layer is negatively charged and has cations as counter ions. When salt is present in the outside of the heterocore portion, the cations constituting the salt exchange with the cations contained in the polycation layer, and depending on the salt concentration, the cations constituting the salt penetrate into the polyanion layer. As a result, the polyanion layer swells or shrinks, changing the refractive index.
[0023] The salt sensor device of the present invention Manufacturing method an optical fiber comprising an optical transmission section having a core and a clad, and a hetero core section having a core and a clad respectively connected to the core and the clad of the optical transmission section, the core of the hetero core section having a smaller diameter than the core of the optical transmission section A method for manufacturing a salt sensor device comprising:The method further comprises a step of forming a metal nanoparticle layer on the outer peripheral surface of the heterocore portion, and then repeating an operation of forming a polyion layer on the metal nanoparticle layer at least twice to form an inorganic-organic composite laminated film in which a plurality of metal nanoparticle layers and polyion layers covering the metal nanoparticle layers are alternately laminated, the polyion layer being characterized in that the polyion layer is made of a polycation selected from the group consisting of vinylpyrrolidone-N,N-dimethylaminoethyl methacrylic acid copolymer diethyl sulfate, chitosan, diethylaminoethyl dextran, diallylamine hydrochloride polymer, methyldiallylamine hydrochloride polymer, diethylaminoethyl cellulose, and dextran chloride hydroxypropyltrimethylammonium ether, or a polyanion selected from the group consisting of polyglutamic acid and its salts, carboxymethyl dextran, carboxymethyl cellulose, hyaluronic acid and its salts, and alginic acid and its salts. 。 [Brief description of the drawings]
[0024] [Figure 1] FIG. 2 is an explanatory cross-sectional view showing the configuration of a sensor unit of the salt sensor device of the present invention. [Diagram 2] FIG. 2 is an explanatory diagram showing the device configuration of the salt sensor device of the present invention. [Diagram 3] 4 is an explanatory cross-sectional view showing a method for measuring the concentration of a sodium chloride solution using the salt sensor device of the present invention. FIG. [Figure 4] Graph showing the relationship between the intensity (loss) of transmitted light (reflected light) and the concentration of sodium chloride solution 5 minutes after adding a sodium chloride solution of a given concentration to distilled water. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] Next, embodiments of the present invention will be described in more detail with reference to the accompanying drawings.
[0026] 1, the salt sensor device 1 of this embodiment includes an optical fiber 4 having a hetero core portion 3 of a predetermined length sandwiched between light transmission portions 2, 2. The light transmission portion 2 is a multimode optical fiber consisting of a core 5a and a cladding 6a that covers the outer peripheral surface of the core 5a, and the hetero core portion 3 is a single-mode optical fiber consisting of a core 5b having a smaller diameter than the core 5a and a cladding 6b that covers the outer peripheral surface of the core 5b.
[0027] The salt sensor device 1 includes an inorganic-organic composite laminated film 7 formed on the outer peripheral surface of the clad 6b of the heterocore portion 3. In this embodiment, the inorganic-organic composite laminated film 7 is formed by alternately laminating a plurality of metal nanoparticle layers, for example, 2 to 2000 metal nanoparticle layers, and a plurality of polyion layers, for example, 2 to 2000 polyion layers, and the metal nanoparticle layers are made of metal nanoparticles having a particle diameter in the range of 5 to 100 nm. The polyion layer may be a positively charged polycation layer or a negatively charged polyanion layer.
[0028] In the salt sensor device 1 of this embodiment, when light is transmitted through the core 5a of the light transmission section 2, evanescent light seeps out to the outside world when the light leaking into the cladding 6b in the heterocore section 3 is totally reflected at the interface between the cladding 6b and the outside world, and when the evanescent light resonates with the collective vibration of electrons in the metal nanoparticles of the metal nanoparticle layer constituting the inorganic-organic composite laminated film 7, the evanescent light is absorbed and the reflected light totally reflected at the interface is reduced. Here, the degree of reduction in the reflected light depends on the refractive index of the polyion layer constituting the inorganic-organic composite laminated film 7, and the refractive index changes depending on the concentration of salt present in the outside world of the heterocore section.
[0029] Therefore, according to the salt sensor device 1, the concentration of salt present in the outside world of the hetero core portion 3 can be known by detecting the degree of reduction in light totally reflected at the interface between the cladding 6b of the hetero core portion 3 and the outside world.
[0030] 2, in the salt sensor device 1 of this embodiment, when the heterocore portion 3 of the optical fiber 4 is buried inside the concrete 21 of a bridge, tunnel, building, or the like, a light source 22 such as an LED is connected to one end of the optical fiber 4, and a detection device 23 such as a spectrum analyzer is connected to the other end of the optical fiber 4. In addition, an analysis device 24 such as a personal computer that analyzes the degree of reduction in reflected light detected by the detection device 23 is connected to the detection device 23. The light source 22, the detection device 23, and the analysis device 24 can be disposed at a location away from where the heterocore portion 3 is buried.
[0031] According to the salt sensor device 1 shown in Fig. 2, light having a wavelength in the range of 300 to 1000 nm, for example, 425 nm, is irradiated from the light source 22 and enters the core 5a of the light transmission section 2, and the reflected light that is totally reflected at the interface between the cladding 6b of the hetero core section 3 and the outside world exits the core 5a of the light transmission section 2 and is received by the detection device 23. In the salt sensor device 1 shown in Fig. 2, the reflected light received by the detection device 23 is analyzed by the analysis device 24, and the salt concentration in the concrete 21 can be detected from the degree of reduction.
[0032] It is known that concrete and the steel framework inside it deteriorate due to sodium chloride contained in seawater and calcium chloride contained in antifreeze. However, the salt sensor device 1 shown in Figure 2 can detect the concentration of salts such as sodium chloride and calcium chloride in concrete 21 using InSuti, thereby enabling the deterioration of concrete and the steel framework inside it to be properly managed.
[0033] The salt sensor device 1 can be manufactured, for example, as follows.
[0034] First, the cladding 6b of the heterocore 3 of the optical fiber 4 is treated with a silane coupling agent such as 3-aminopropyltrimethoxysilane to introduce amino groups onto the surface of the cladding 6b. Next, the heterocore 3 with the amino groups introduced onto the surface of the cladding 6b is immersed in pure water to protonate the amino groups.
[0035] Next, the hetero core portion 3 in which the amino group introduced on the surface of the clad 6b is protonated is immersed in a metal nanoparticle suspension. In this way, a metal nanoparticle layer consisting of the metal nanoparticles can be formed on the outer peripheral surface of the clad 6b due to the interaction between the positive charge of the protonated amino group and the negative charge on the surface of the metal nanoparticle. For example, when the metal nanoparticles are gold nanoparticles, the metal nanoparticle suspension can be prepared by adding a predetermined concentration of citric acid, sodium citrate, or potassium citrate and a predetermined concentration of gold tetrachloride (III) in boiling water in predetermined amounts and stirring.
[0036] Next, the heterocore portion 3 with the metal nanoparticle layer formed on the outer peripheral surface of the clad 6b is immersed in a polyion aqueous solution of a predetermined concentration for a predetermined time, and then pulled out and washed, thereby forming the polyion layer on the metal nanoparticle layer. Washing after immersing the heterocore portion 3 in the polyion aqueous solution can be performed by immersing the heterocore portion 3 in pure water and gently moving it. Note that when the polyion layer is a polycation layer, the polyion aqueous solution is a polycation aqueous solution, and when the polyion layer is a polyanion layer, the polyion aqueous solution is a polyanion aqueous solution.
[0037] The polycations used in the polycation aqueous solution include Polycations selected from the group consisting of vinylpyrrolidone-N,N-dimethylaminoethyl methacrylic acid copolymer diethyl sulfate, chitosan, diethylaminoethyl dextran, diallylamine hydrochloride polymer, methyl diallylamine hydrochloride polymer, diethylaminoethyl cellulose, and dextran chloride hydroxypropyltrimethylammonium ether Examples include:
[0038] The polycation layer formed by the polycation aqueous solution has anions as counter ions, and when salt is present in the external environment of the heterocore portion 3, the anions constituting the salt exchange with the anions contained in the polycation layer, and depending on the salt concentration, the anions constituting the salt penetrate the polycation layer, causing the polycation layer to swell or shrink, changing its refractive index. Therefore, when the salt sensor device 1 of this embodiment is used to detect sodium chloride, it is preferable that the counter anions are other than chloride ions, and it is preferable that the polycation layer does not contain chloride ions as counter ions.
[0039] On the other hand, the polyanion used in the polyanion aqueous solution is A polyanion selected from the group consisting of polyglutamic acid and its salts, carboxymethyldextran, carboxymethylcellulose, hyaluronic acid and its salts, and alginic acid and its salts. Examples include:
[0040] The polyanion layer formed by the polyanion aqueous solution has cations as counter ions, and when salt is present in the external environment of the heterocore portion 3, the cations constituting the salt undergo ion exchange with the cations contained in the polyanion layer, and depending on the salt concentration, the cations constituting the salt penetrate the polyanion layer, causing the polyanion layer to swell or shrink, changing its refractive index. Therefore, when the salt sensor device 1 of this embodiment is used to detect sodium chloride, it is preferable that the counter cation is other than sodium ion, and it is preferable that the polyanion layer does not contain sodium ion as the counter ion. In the manufacturing method of the salt sensor device 1 of this embodiment, the operation of forming the metal nanoparticle layer and the operation of forming the polyion layer are repeated 2 to 2000 times, thereby forming the inorganic-organic composite laminated film 7 in which 2 to 2000 layers of metal nanoparticle layers and 2 to 2000 layers of polyion layers are alternately laminated one by one.
[0041] Next, examples and comparative examples will be described. EXAMPLES
[0042] [Example] In this example, 100 ml of distilled water was first boiled, and 1 ml of a 1% by mass citric acid solution and 1 ml of a 1% by mass tetrachloroaurate (III) acid solution were added thereto, and the mixture was stirred for 15 minutes while still boiling to prepare a gold nanoparticle suspension. The gold nanoparticle suspension contains gold nanoparticles with particle diameters ranging from 5 to 100 nm and negatively charged surfaces.
[0043] Next, 50 mL of a 1% by mass aqueous solution of acetic acid was heated to a temperature of 40° C., 0.5 mL of 3-aminopropyltrimethoxysilane as a silane coupling agent was added, and the heterocore portion of the optical fiber 4 was immersed in the solution for 2 minutes while gently stirring. Next, the heterocore portion 3 was heated at a temperature of 110° C. for 2 hours, and amino groups were introduced into the surface of the cladding 6b of the heterocore portion 3.
[0044] Next, the heterocore portion 3 having amino groups introduced on the surface of the cladding 6b was immersed in pure water to protonate the amino groups.
[0045] Next, the heterocore portion 3 in which the amino group introduced onto the surface of the clad 6b was protonated was immersed in the gold nanoparticle suspension prepared in this example, to form a gold nanoparticle layer on the outer surface of the clad 6b.
[0046] Next, the heterocore portion 3 with the gold nanoparticle layer formed on the outer surface of the cladding 6b was immersed in a vinylpyrrolidone-N,N-dimethylaminoethyl methacrylic acid copolymer diethyl sulfate aqueous solution having a concentration in the range of 20 mmol / L as a polycation aqueous solution, then pulled out and washed with pure water to form a polycation layer on the gold nanoparticle layer.
[0047] In this example, the operation of forming the gold nanoparticle layer and the operation of forming the polycation layer were repeated five times to form an inorganic-organic composite laminated film 7 in which five gold nanoparticle layers and five polycation layers were alternately laminated one by one, thereby obtaining the salt sensor device 1 shown in Figure 1.
[0048] Next, in the salt sensor device 1 shown in Fig. 1, the heterocore portion 3 having the inorganic-organic composite laminated film 7 on the outer peripheral surface of the cladding 6b was immersed in distilled water 26 contained in a container 25 as shown in Fig. 3, instead of being embedded in concrete 29 as shown in Fig. 2. Next, aqueous sodium chloride solutions of predetermined concentrations were successively added to the distilled water 26 to turn the distilled water 26 into an aqueous sodium chloride solution, while varying the concentration.
[0049] Next, for the heterocore portion 3 immersed in the sodium chloride aqueous solution of each concentration 5 minutes after adding the sodium chloride aqueous solution of a predetermined concentration, light with a wavelength of 425 nm was irradiated from the light source 22 into the core 5a of the light transmission portion 2, and the reflected light that was totally reflected at the interface between the cladding 6b of the heterocore portion 3 and the outside world was emitted from the core 5a of the light transmission portion 2, and the reflected light received by the detection device 23 was analyzed by the analysis device 24.
[0050] Next, the loss in the intensity of propagated light (reflected light) when the heterocore portion 3 was immersed in the sodium chloride aqueous solution (hereinafter abbreviated as "loss in propagated light intensity") relative to the propagated light (reflected light) intensity when the heterocore portion 3 was in air was calculated for each concentration of the sodium chloride aqueous solution using the following formula (1). The results are shown in Table 1 and Figure 4.
[0051] In Table 1, the numerical values of the examples and comparative examples are the loss of the propagation light intensity (dB). In addition, in Fig. 4, the loss of the propagation light intensity is shown as "Propagation light intensity (dB) 5 minutes after addition of NaCl."
[0052] Loss of transmitted light intensity (dB) = 10 × log 10 (Propagated light intensity when the heterocore portion 3 is immersed in a sodium chloride aqueous solution 26 / Propagated light intensity when the heterocore portion 3 is in air) (1) Comparative Example In this comparative example, 100 ml of distilled water was first boiled, and 1 ml of a 1% by mass aqueous solution of citric acid and 1 ml of a 1% by mass aqueous solution of tetrachloroauric acid (III) were added thereto, and the mixture was stirred for 15 minutes while still boiling to prepare a gold nanoparticle suspension. The gold nanoparticle suspension contains gold nanoparticles with particle diameters ranging from 5 to 100 nm and negatively charged surfaces.
[0053] Next, 50 mL of a 1% by mass aqueous solution of acetic acid was heated to a temperature of 40° C., 0.5 mL of 3-aminopropyltrimethoxysilane as a silane coupling agent was added, and the heterocore portion of the optical fiber 4 was immersed in the solution for 2 minutes while gently stirring. Next, the heterocore portion 3 was heated at a temperature of 110° C. for 2 hours, and amino groups were introduced into the surface of the cladding 6b of the heterocore portion 3.
[0054] Next, the heterocore portion 3 having amino groups introduced on the surface of the cladding 6b was immersed in pure water to protonate the amino groups.
[0055] Next, the heterocore portion 3 in which the amino group introduced onto the surface of the clad 6b was protonated was immersed in the gold nanoparticle suspension prepared in this comparative example to form a gold nanoparticle layer on the outer peripheral surface of the clad 6b.
[0056] Next, the heterocore 3 with the gold nanoparticle layer formed on the outer peripheral surface of the clad 6b was immersed in a vinylpyrrolidone-N,N-dimethylaminoethyl methacrylic acid copolymer diethyl sulfate aqueous solution with a concentration in the range of 20 millimoles / liter as a polycation aqueous solution, pulled out and washed with pure water, and then immersed in a polyvinyl potassium sulfate aqueous solution with a concentration in the range of 20 millimoles / liter as a polyanion aqueous solution, pulled out and washed with pure water. This operation was repeated 20 times to form an alternating laminated film in which 20 layers of polycation layers and 20 layers of polyanion layers were alternately laminated. As a result, a salt sensor device was obtained that had only one gold nanoparticle layer on the outer peripheral surface of the clad 6b and the alternating laminated film covering the gold nanoparticle layer.
[0057] Next, the loss of the transmitted light intensity for each concentration of the sodium chloride aqueous solution was calculated in exactly the same manner as in the above-mentioned Example, except that the salt sensor device obtained in this Comparative Example was used. The results are shown in Table 1 and FIG.
[0058] [Table 1] The variation width, which is the difference between the maximum and minimum values of the loss in the propagation light intensity, was calculated from the values shown in Table 1. In the embodiment, the variation width is (-2.214)-(-2.6286)=0.4146(dB) In the comparative example, (-2.0395)-(-2.3113)=0.2718(dB) It is.
[0059] Therefore, it is clear that the sensitivity of the salt sensor device 1 of the embodiment is increased by 0.4146 / 0.2718=1.53 (times) compared to the salt sensor device of the comparative example. [Explanation of symbols]
[0060] REFERENCE SIGNS LIST 1...salt sensor device, 2...light transmission section, 3...heterocore section, 4...optical fiber, 5a, 5b...core, 6a, 6b...clad, 7...inorganic-organic composite laminated film.
Claims
1. A salt sensor device comprising an optical fiber including a light transmitting section having a core and a clad, and a hetero core section having a core and a clad respectively connected to the core and the clad of the light transmitting section, the core of the hetero core section having a smaller diameter than the core of the light transmitting section, a plurality of metal nanoparticle layers and a plurality of polyion layers covering the metal nanoparticle layers are alternately laminated on an outer peripheral surface of the clad of the heterocore portion, The polyion layer is made of a polycation selected from the group consisting of vinylpyrrolidone-N,N-dimethylaminoethyl methacrylic acid copolymer diethyl sulfate, chitosan, diethylaminoethyl dextran, diallylamine hydrochloride polymer, methyldiallylamine hydrochloride polymer, diethylaminoethyl cellulose, and dextran chloride hydroxypropyltrimethylammonium ether, or a polyanion selected from the group consisting of polyglutamic acid and its salts, carboxymethyl dextran, carboxymethyl cellulose, hyaluronic acid and its salts, and alginic acid and its salts.
2. 2. The salt sensor device according to claim 1, wherein the inorganic-organic composite laminated film is formed by alternately laminating 2 to 2000 layers of the metal nanoparticle layers and the polyion layers.
3. 3. The salt sensor device according to claim 1, wherein the metal nanoparticles constituting the metal nanoparticle layer have a particle diameter in the range of 5 to 100 nm.
4. 4. The salt sensor device according to claim 3, wherein the metal nanoparticles are gold nanoparticles.
5. A method for manufacturing a salt sensor device comprising an optical fiber including a light transmitting section having a core and a clad, and a hetero core section having a core and a clad respectively connected to the core and the clad of the light transmitting section, the core of the hetero core section having a smaller diameter than the core of the light transmitting section, a step of forming a metal nanoparticle layer on the outer peripheral surface of the heterocore portion, and then repeating an operation of forming a polyion layer on the metal nanoparticle layer at least twice to form an inorganic-organic composite laminated film in which a plurality of metal nanoparticle layers and polyion layers covering the metal nanoparticle layers are alternately laminated, The method for manufacturing a salt sensor device is characterized in that the polyion layer is made of a polycation selected from the group consisting of vinylpyrrolidone-N,N-dimethylaminoethyl methacrylic acid copolymer diethyl sulfate, chitosan, diethylaminoethyl dextran, diallylamine hydrochloride polymer, methyldiallylamine hydrochloride polymer, diethylaminoethyl cellulose, and dextran chloride hydroxypropyltrimethylammonium ether, or a polyanion selected from the group consisting of polyglutamic acid and its salts, carboxymethyl dextran, carboxymethyl cellulose, hyaluronic acid and its salts, and alginic acid and its salts.
Citation Information
Patent Citations
Fungicidal composition
JP1988091305A
Optical fiber type measurement method and optical fiber type measurement device
JP2015203692A
Optical fiber sensor device
JP2015232522A
Refractive index measurement device and method
JP2019039723A
Fiber-optic sensor or modulator using tuning of long period gratings with self-assembled layers
US20070025661A1